Adult's perception of health care after myocardial infarction - Vanêssa Piccinin Paz; Maria de Fátima Mantovani; Nen Nalú Alves das Mercês; Verônica de Azevedo Mazza; Ângela Taís Mattei da Silva (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to describe the Adult's perception of healthcare after Myocardium Infarction. Methods: qualitative descriptive analysis carried out with 12 adults who had myocardial infarction and conducted from February to May 2018. The research design was based on the "Consolidated Criteria for Reporting Qualitative Research". Data collection was performed through semi-structured questionnaire, interview script and field diary. The interviews were encoded, and their content was analyzed using software support. Results: three classes were obtained: "Fear, (un) certainty and (un) awareness"; "Lifestyle and beliefs of illness" and "Health care search". Unhealthy lifestyle habits, lack of health prevention / promotion, difficulties in accessing services and lack of knowledge about the disease generated fear and uncertainty about the future. Final Considerations: the perception of acute myocardial infarction is related to the trajectory of illness, lifestyle and the belief that the infarction only affects others.